2021
DOI: 10.2147/prbm.s302697
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Academic Engagement in Adolescents: The Mediating Role of Self-Esteem

Abstract: Background: Academic engagement is a variable of vital importance in adolescence due to its relationship with academic adjustment and its protective role against risk behaviors. Therefore, the objective of this study was to find out the variables involved in its development. Objective: The specific objectives were to analyze the relationship between emotional intelligence, self-esteem and academic engagement, and determine the mediating role of selfesteem in the relationship between emotional intelligence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
7
0
6
Order By: Relevance
“…Ability EI is conceptualized as a form of intelligence and hence it should predict more theoretical aspect of grades, such as general professional knowledge. Furthermore, research has already shown that students who can more effectively manage emotions better adapt to the school context and schoolwork, making them feel more connected with their institution (Barragan Martin et al, 2021). Hence, we argue that engagement with the school could play a role in explaining the link between ability EI and grades.…”
Section: The Present Studymentioning
confidence: 79%
“…Ability EI is conceptualized as a form of intelligence and hence it should predict more theoretical aspect of grades, such as general professional knowledge. Furthermore, research has already shown that students who can more effectively manage emotions better adapt to the school context and schoolwork, making them feel more connected with their institution (Barragan Martin et al, 2021). Hence, we argue that engagement with the school could play a role in explaining the link between ability EI and grades.…”
Section: The Present Studymentioning
confidence: 79%
“…This is the conclusion reached by a number of researchers. It has been suggested by (Martínez et al, 2023) that one of the potential reasons for depersonalization among nurses is that they may not have appropriate coping strategies in place. There is also the possibility that individuals who are alexithymia prefer to pay more attention to what is going on around them rather than to how it makes them feel.…”
Section: Discussionmentioning
confidence: 99%
“…This group of students also has a more stable emotional state when facing unexpected situations and has more confidence to start the next level of learning, improving their self-esteem in a gradual process. 35 Students with poor academic adaptability tend to experience more stress and depression in their daily academic life, lacking positive affirmative evaluations and proper emotional relief, which in the long run tends to lead to a decline in both their academic performance and self-esteem levels. 62 Students with low self-esteem are more at risk for social and emotional difficulties, which prevents them from being fully engaged in their studies, resulting in poor academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The higher level of students’ academic adaptability, the higher their self-esteem level will be. 35 There is a correlation between academic adaptability and self-esteem. In addition, students with low self-esteem levels always refer to themselves in a negative way, placing themselves in a disadvantaged “weak mentality”.…”
Section: Introductionmentioning
confidence: 99%